Development of MAKID (Interactive Digital Learning Media for Mathematics) to Enhance the Cognitive Abilities of 5 to 6-Year-Old Children with ADHD in Kindergarten - Hana Kuswo Putri; Wagino Wagino; Ainur Rifqi (Journal of General Education and Humanities, 2026)
Attention Deficit Hyperactivity Disorder (ADHD) can affect children's concentration, learning, participation, and cognitive development, particularly in understanding basic mathematical concepts. This study aimed to develop and evaluate MAKID (Math Interactive Kids Digital) as an interactive digital mathematics learning application designed to enhance the cognitive abilities of children with ADHD. The research employed a Research and Development (R&D) approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. The study was conducted at The Baby School Tuban Kindergarten and involved six children with ADHD aged 5–6 years, as well as special education, mathematics, media, and classroom practitioners. Data were collected through observations, interviews, expert validation sheets, and pre-test and post-test assessments. The developed application contains four mathematics learning modules, namely numbers, shapes, sizes, and patterns, supported by interactive activities and self-regulation features specifically adapted to the characteristics of children with ADHD. The results indicated that the application was valid and feasible for use, based on expert evaluations, and demonstrated effectiveness in improving children's mathematical cognitive performance, as reflected in higher post-test scores than pre-test scores. The novelty of this study lies in the development of an ADHD-centered digital learning application that integrates cognitive stimulation strategies with interactive mathematics instruction. Therefore, MAKID has the potential to serve as an innovative educational medium to support mathematics learning and cognitive development among children with ADHD.